Penerapan Teknik Citra Digital Sebagai Metode Pengukuran Morfometrik Ternak Pada Sapi Bali dan Peranakan Ongole - Bramada Winiar Putra; Asnath Maria Fuah; Henny Nuraini; Rudy Priyanto (Institut Pertanian Bogor, 2016)
Morphometric measurements using digital image technique give a lot of benefits i.e., a safer method both for the researchers and the experimental animals, produce a more accurate morphometric data, reduce the stress in the experimental animals and produce a more detail and complete morphometric data. This experiment used 20 Ongole cross cattle and 20 Bali cattle with the average age of 3 years. Digital image data were collected by using DSLR camera with 18Mp resolution. The collected digital image data were analyzed by using Image J program. Parameters measured in this observation were body length, body height, hip height, pelvic height, loin height, the length of ossa vertebrae cervicales, the length of ossa vertebrae thoracicae, the length of ossa vertebrae lumbales, the length of os scapula, the length of os humerus, the length of ossa radius-ulna, the length of os metacarpale III, the length of os femoris, the length of ossa tibia-fibula, and the length of os metatarsale III. Digital image technique could replace the manual technique for morphometric measurement with a lower level of variance (<10%). Application of digital image technique for measurement of morphometric parameters in Ongole Cross and Bali cattle showed that Bali cattle has a potential for muscle deposition in body frame and body axis while Ongole Cross cattle has a potential for muscle deposition in fore and hind legs.